2017
DOI: 10.1053/j.gastro.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sessile Serrated Adenomas in the Proximal Colon Using Wide-Field Fluorescence Endoscopy

Abstract: Background & Aims Many cancers in the proximal colon develop via from sessile serrated adenomas (SSAs), which have flat, subtle features that are difficult to detect with conventional white-light colonoscopy. Many SSA cells have the V600E mutation in BRAF. We investigated whether this feature could be used with imaging methods to detect SSAs in patients. Methods We used phage display to identify a peptide that binds specifically to SSAs, using subtractive hybridization with HT29 colorectal cancer cells conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 45 publications
0
47
0
Order By: Relevance
“…In this report, the authors were able to show that SSAs had >2 higher fluorescence intensity during fluorescence colonoscopy compared to normal colonic mucosa and that molecular imaging with topically applied KCCFPAQ distinguished SSAs from normal colonic mucosa with high sensitivity and specificity (Fig. ) . Hence, this targeted imaging approach might be used to facilitate early detection of premalignant serrated lesions during routine colonoscopies.…”
Section: Components Of Molecular Imagingmentioning
confidence: 71%
See 3 more Smart Citations
“…In this report, the authors were able to show that SSAs had >2 higher fluorescence intensity during fluorescence colonoscopy compared to normal colonic mucosa and that molecular imaging with topically applied KCCFPAQ distinguished SSAs from normal colonic mucosa with high sensitivity and specificity (Fig. ) . Hence, this targeted imaging approach might be used to facilitate early detection of premalignant serrated lesions during routine colonoscopies.…”
Section: Components Of Molecular Imagingmentioning
confidence: 71%
“…Hence, SSAs represent lesions that can be challenging to detect and means to improve and facilitate SSA detection are certainly needed. In a recent study, Joshi and co‐workers identified the peptide KCCFPAQ which exhibited specific binding to SSA . In this report, the authors were able to show that SSAs had >2 higher fluorescence intensity during fluorescence colonoscopy compared to normal colonic mucosa and that molecular imaging with topically applied KCCFPAQ distinguished SSAs from normal colonic mucosa with high sensitivity and specificity (Fig.…”
Section: Components Of Molecular Imagingmentioning
confidence: 72%
See 2 more Smart Citations
“…Histopathological investigations of microsatellite instable, proximal, and interval CRCs may help identify the features of high-risk premalignant lesions and have important implications for screening, surveillance, and treatment. Also, the development of technologies that improve detection and/or resection of SPs would be welcome tools to prevent CRC arising from serrated precursors, and there are some compelling recent reports along these lines [73]. …”
Section: What Are the Areas Of Uncertainty Related To Surveillance Ofmentioning
confidence: 99%